Modelling Literacy Program Management: Innovation in Building Student's Reading Culture at Elementary Schools - Purtri, Rizka Fichia; Nisa, Choirun (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to describe the management of the Modeling Literacy Program as an innovation to foster a reading culture among third-grade students at SDN 2 Gledeg Klaten.Methodology: This study uses a qualitative approach. Data were collected through observation, interviews, and documentation involving teachers, students, and parents. Data validity was tested through triangulation of sources and techniques to obtain accurate and reliable information.Results: The results of the study show that 1) Teachers play an important role in managing literacy activities through four stages: planning, organization, actuating, and controlling. 2) Parents' opinions indicate that teachers' active involvement in literacy activities increases children's enthusiasm for reading and strengthens cooperation between schools and families. 3) Students' responses indicate that teachers' exemplary behavior makes reading activities more enjoyable, builds self-confidence, and forms independent reading habits. This program is effective in increasing interest in reading, strengthening teacher-student interaction, and encouraging parental involvement in literacy at home.Applications/Originality/Value: This Model-Based Literacy Program provides a practical literacy management model that integrates teacher leadership, student participation, and parent collaboration. This innovation increases student motivation to read and strengthens the partnership between schools and families in building a sustainable literacy culture. These findings can be used as a reference for elementary schools in implementing effective education management.